Study of Institution Model of Micro Finance to Raise Children Opportunities of Poor Families for Having Higher Education: Perception and Effort of Poor Households - Khusnul Ashar; Susilo Susilo; Al Muizzuddin Fazaalloh (Institute of Research and Community Service, University of Brawijaya)
The aim of this research is for making micro financial institution that is healthy and sustainable with basic of local institution. Moreover, this research encourages the children of poor families to continue study to higher education. This research is performed within 3 years in Malang Regency. On the first year, this research identified the perception of poor families. The kinds of the perception are the role of higher education, the effort for preparing the future of children, and how far the role of local finance institution. The sample used in this research are 100 units of poor households which are taken purposively and analyzed with frequency distribution method. This research found that: (1) poor families have positive perception about higher education, (2) the majority of poor families (97%) have desired the children could continue study to higher education, (3) the motivation of poor families to get the children continue the study to higher education basically based on the better of children’s future, better knowledge, and better job, (4) Specifically, the efforts of poor families to make the children could continue to higher education are to save more income, to do more hard work, to give motivation to the children, and to find scholarships, (5) the role of local finance institution like cooperation is very small to support poor families to make the children to continue their study.Keywords: Micro finance institution, Poverty, Higher Education